YMCA Indian Guides Apache Tribe at Sequoia Lake - Watkins, Howard::::::::: (1988)
Apache Tribe group photo: front ???Josiah Gordon, Jared Gordon, Adam Watkins, and ?' Back ??, Dean Gordon, Howard Watkins, and /